The fundamental right of access to medicines and the social function of intangible property in Brazil - Batista, Cláudia Karina Ladeia; Calil, Mário Lúcio Garcez (Journal of Health Law, 2016)
This is a literature and documental research aiming at studying the relationship between the right of access to medicines and the right to exclusivity in the exploitation of pharmaceutical inventions, from the fundamental right to health in its various dimensions. This study is justified by the increasing importance that the access to medicines currently has in the fundamental right to health, and by the necessity of balancing this right with the patents, if seen that all property, including intangible, has a social function. We conclude that it is necessary to harmonize the right to preserve intangible property –and, as a consequence, to preserve the economic exclusive exploitation of a developed and patented product- with the right of access to medicines, at risk of losing both constitutional guarantees.